Vagus nerve stimulation: state of the art of stimulation and recording strategies to address autonomic function neuromodulation. (28th June 2016) - Guiraud, David; Andreu, David; Bonnet, Stéphane; Carrault, Guy; Couderc, Pascal; Hagège, Albert; Henry, Christine; Hernandez, Alfredo; Karam, Nicole; Le Rolle, Virginie; Mabo, Philippe; Maciejasz, Paweł; et al.
Abstract: Objective. Neural signals along the vagus nerve (VN) drive many somatic and autonomic functions. The clinical interest of VN stimulation (VNS) is thus potentially huge and has already been demonstrated in epilepsy. However, side effects are often elicited, in addition to the targeted neuromodulation. Approach. This review examines the state of the art of VNS applied to two emerging modulations of autonomic function: heart failure and obesity, especially morbid obesity. Main results. We report that VNS may benefit from improved stimulation delivery using very advanced technologies. However, most of the results from fundamental animal studies still need to be demonstrated in humans.